Trajectories of depressive symptoms in older adults and associated health outcomes - Agustini, B.; Lotfaliany, M.; Mohebbi, M.; Woods, R.L.; McNeil, J.J.; Nelson, M.R.; Shah, R.C.; Murray, A.M.; Reid, Christopher; Tonkin, A.; Ryan, J.; Williams, L.J.; et al. (2022)
With the progressive aging of the world’s population, prolongation of a healthy lifespan in old age has become a medical research priority. The presence of depressive symptoms in later life is associated with poor health prognosis and increased mortality1,2. Here we explore distinct trajectories of depressive symptoms in later life and their association with several health-related outcomes in 19,110 older individuals followed for a median of 4.7 years. Using a latent class, mixed-modeling approach we identified four distinct trajectories of depressive symptoms with scoring patterns of consistently low, moderate, emerging and persistently high. Compared to those with minimal depressive symptoms, membership of any other class was associated with specific patterns of baseline sociodemographic and medical factors. Membership of any group with depressive symptoms was associated with a higher likelihood of health events, including physical disability, cancer and major bleeding episodes. Membership of the persistently depressed class was associated with increased mortality, while a diagnosis of dementia was generally limited to the class with initially low and progressively rising symptoms. The course of depressive symptoms in older individuals can vary widely and depend on several factors. The presence of depressive symptoms, including those that do not meet criteria for major depression, can flag a poor prognosis and risk for specific health conditions. Systematic assessment of depressive symptoms may facilitate early identification of at-risk populations.